Implementation of the P5 Project in Forming Ecological Citizenship at a Junior High School in Palangka Raya - Ikhsan, Ibnu; Triyani, Triyani; Agussana, Agussana (Faculty of Humanities, Universitas Jenderal Soedirman, 2024)
This study aims to explore the implementation of the Pancasila Student Profile Strengthening Project (P5) at a Junior High School in Palangka Raya, with a focus on developing students' characters who care about the environment. Using a descriptive qualitative approach, data was collected through interviews with the P5 coordinator and observations over three months. The results showed that the garden-building project taught students about cooperation and responsibility and provided practical gardening and time management skills. Despite weather changes, budget limitations, and time management challenges, students still showed high enthusiasm and commitment. The project is an effective means of character education, forming students who care about the environment and have a spirit of cooperation. It is hoped that this experience can equip students with a positive and sustainable attitude in maintaining cleanliness and environmental sustainability in the future, which aligns with P5's goal of creating good citizenship.